Terahertz-field-induced ionization effect in a single nano island - Seo, Minah (ULTRAFAST PHENOMENA AND NANOPHOTONICS XX, 2016)
In this report, we present a novel approach to exploit the nonlinear response of terahertz (THz) field allowing the observation of ionization phenomenon in a single metal nano island. Because it is not easy to access such high power THz source to generate field over the threshold of the materials, fundamental studies on nonlinear terahertz waves and their applications in spectroscopy have been limited thus far. We are able to overcome this limitation through the use of a metallic nano island embedded in a slot antenna which strongly confines the terahertz electric field driving the system into a highly nonlinear regime. The structure, composed of a nano slot antenna and a nano island located at the center, highly confines THz electromagnetic field at the center of the structure, resulting in huge field enhancement by orders of magnitude at a specific frequency. Electrons on a metallic surface experience a ponderomotive force in a highly confined and enhanced THz electric field directed towards the weak field area by a field gradient. As a result, the accelerated electrons acquire enough energy to ionize ambient carbon atoms. It has to be stressed that it is the first time to observe the ionization of atoms induced by the enhanced terahertz radiation.